Acequias and the Effects of Climate Change. (August 2013) - Rango, Albert; Fernald, Alexander; Steele, Caitriana; Hurd, Brian; Ochoa, Carlos
Abstract Traditional forms of acequia irrigation can be combined with ground based and remote sensing snow measurements and snowmelt runoff modeling to better estimate runoff volumes now and in the future under conditions of climate change. The experience gained over 400 years of irrigating small fields strongly binds communities and strengthens the resolve of acequia associations to contest challenges presented by climate change. Increased density of snow measurements in high elevations of the Rio Grande along with input of real‐time data to snowmelt models has led to an improved potential for acequia decision making under the increased temperatures projected for the future by climate models. Acequia communities and similar Native American settlements have shown the willingness to share water during times of severe water shortages in the southwestern U.S. Acequia associations have shown the desire to adopt new forms of hydrologic data and modeling techniques and incorporate them into acequia association approaches.